2022
DOI: 10.1101/2021.12.31.474653
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The altered entry pathway and antigenic distance of the SARS-CoV-2 Omicron variant map to separate domains of spike protein

Abstract: At the end of 2021 a new SARS-CoV-2 variant, Omicron, emerged and quickly spread across the world. It has been demonstrated that Omicrons high number of Spike mutations lead to partial immune evasion from even polyclonal antibody responses, allowing frequent re-infection and vaccine breakthroughs. However, it seems unlikely these antigenic differences alone explain its rapid growth; here we show Omicron replicates rapidly in human primary airway cultures, more so even than the previously dominant variant of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
344
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 302 publications
(382 citation statements)
references
References 83 publications
(141 reference statements)
26
344
4
1
Order By: Relevance
“…5a). These ndings suggests Omicron spike preferentially enter through ACE2-mediated endocytosis and this is in support with recent studies which showed Omicron preferentially enters cells by endocytic pathway 29,51 . In contrast, highly virulent variants like Delta could use both a) endocytic pathway and activation of S1/S2 protein mediated by Cathepsin B/L proteases and b) cell surface entry by activation of S1/S2 using serine protease TMPRSS2.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…5a). These ndings suggests Omicron spike preferentially enter through ACE2-mediated endocytosis and this is in support with recent studies which showed Omicron preferentially enters cells by endocytic pathway 29,51 . In contrast, highly virulent variants like Delta could use both a) endocytic pathway and activation of S1/S2 protein mediated by Cathepsin B/L proteases and b) cell surface entry by activation of S1/S2 using serine protease TMPRSS2.…”
Section: Discussionsupporting
confidence: 91%
“…Peacock. P.T et, al and group have recently shown 29 , Omicron viruses usage TMPRSS2 independent entry pathway. In our study, we found both the variants and mutants pseudoviruses entry to host cell is markedly reduced when treated with Cathepsin L inhibitor like E64d (Fig.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…This unusual pattern of mutations results in significant immune escape in vitro and in an enhanced reinfection potential in vivo ( Cele et al, 2021 ; Garcia-Beltran et al, 2021 ; Schmidt et al, 2021 ; Willett et al, 2022 ). Moreover, omicron displays an altered cellular tropism and cell entry mechanism, which depends on the acquisition of an enhanced ability to rely on the TMPRSS2-independent endosomal route ( Peacock et al, 2022 ; Willett et al, 2022 ). It is presently unclear whether and to which extent the XLI insertion provides a contribution to the unique biological properties of this variant.…”
Section: Resultsmentioning
confidence: 99%